Identifying barriers and facilitators for implementing harm reduction strategies for methamphetamine use into hospital settings - Forchuk, Cheryl; Serrato, Jonathan; Scott, Leanne (Frontiers in Health Services, 2023)
Introduction Harm reduction strategies for substance use disorder are not currently offered in Canadian hospitals. Previous research has suggested that substance use may continue to occur which can lead to further complications such as new infections. Harm reduction strategies may be a solution to this issue. This secondary analysis aims to explore the current barriers and potential facilitators for implementing harm reduction into the hospital from the perspective of health care and service providers. Method Primary data was collected from 31 health care and service providers who participated in a series of virtual focus groups and one-to-one interviews regarding their perspectives on harm reduction. All staff were recruited from hospitals in Southwestern Ontario, Canada from February 2021 to December 2021. Health care and service professionals completed a one-time individual interview or a virtual focus group using an open-ended qualitative interview survey. Qualitative data was transcribed verbatim and analyzed using an ethnographic thematic approach. Themes and subthemes were identified and coded based on responses. Findings Attitude and Knowledge, Pragmatics, and Safety/Reduction of Harm were identified as the core themes. Attitudinal barriers such as stigma and lack of acceptance were reported but education, openness and community support were regarded as potential facilitators. Cost, space, time and availability of substances on site were regarded as Pragmatic barriers but potential facilitators such as organizational support, flexible harm reduction services and a specialized team were identified. Policy and liability were perceived as both a barrier and a potential facilitator. Safety and impact of substances on treatment were considered as both a barrier and a potential facilitator but sharps boxes and continuity of care were regarded as potential facilitators. Discussion Although barriers in implementing harm reduction in hospital settings exist, there are opportunities to facilitate change. As identified in this study, feasible and achievable solutions are available. Education on harm reduction for staff was considered to be a key clinical implication in facilitating harm reduction implementation.